APOBEC Mutagenesis and Copy-Number Alterations Are Drivers of Proteogenomic Tumor Evolution and Heterogeneity in Metastatic Thoracic Tumors - Roper, Nitin (Cell Rep, 2019)
Intratumor mutational heterogeneity has been documented in primary non-small-cell lung cancer. Here, we elucidate mechanisms of tumor evolution and heterogeneity in metastatic thoracic tumors (lung adenocarcinoma and thymic carcinoma) using whole-exome and transcriptome sequencing, SNP array for copy-number alterations (CNAs), and mass-spectrometry-based quantitative proteomics of metastases obtained by rapid autopsy. APOBEC mutagenesis, promoted by increased expression of APOBEC3 region transcripts and associated with a high-risk APOBEC3 germline variant, correlated with mutational tumor heterogeneity. TP53 mutation status was associated with APOBEC hypermutator status. Interferon pathways were enriched in tumors with high APOBEC mutagenesis and IFN-γ-induced expression of APOBEC3B in lung adenocarcinoma cells, suggesting that the immune microenvironment may promote mutational heterogeneity. CNAs occurring late in tumor evolution correlated with downstream transcriptomic and proteomic heterogeneity, although global proteomic heterogeneity was significantly greater than transcriptomic and CNA heterogeneity. These results illustrate key mechanisms underlying multi-dimensional heterogeneity in metastatic thoracic tumors.